2012
DOI: 10.1519/jsc.0b013e31825bb4aa
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness Differences Between Prepubescent Boys and Girls

Abstract: The purpose of this study was to analyze in which physical capabilities boys and girls are closer or distant. An additional objective was to find which of the body fat, physical activity, and somatotype factors have a greater effect on prepubescent children's physical fitness. This was a cross-sectional study involving 312 children (10.8 ± 0.4 years). The physical fitness assessment employed sets of aerobic fitness, strength, flexibility, speed, agility, and balance. The boys presented higher values in all sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
32
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 31 publications
10
32
1
7
Order By: Relevance
“…Boys performed better in the mile run and standing broad jump in both grades, indicating better aerobic fitness and lower body power when compared to girls, as reported elsewhere (3,7,23). However, improvements in power from fourth to fifth grade were not detected in either sex.…”
Section: A C C E P T E Dsupporting
confidence: 72%
See 1 more Smart Citation
“…Boys performed better in the mile run and standing broad jump in both grades, indicating better aerobic fitness and lower body power when compared to girls, as reported elsewhere (3,7,23). However, improvements in power from fourth to fifth grade were not detected in either sex.…”
Section: A C C E P T E Dsupporting
confidence: 72%
“…While others have shown greater flexibility in girls (23), it is important to note that fifth and six graders (10.8 ± 0.4 years) were used, and at this point boys were both taller and heavier, which likely eliminated any transient advantage that occurred at the onset of pubescence in girls. Prior to puberty, sex-specific…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Concretely, girls and boys obtained similar scores during the SEBT. Previous studies reported that women showed greater static balance results among adults and greater static balance among prepubescent participants (Karppanen et al, 2012;Marta, Marinho, Barbosa, Izquierdo, & Marques, 2012) and participants aged 20 years (Sekulic et al, 2013). It is probable that the non-signi cant di erences in anthropometric measures (i.e.…”
Section: Resultsmentioning
confidence: 97%
“…Recentemente tem sido apontada a necessidade da investigação considerar a coinfluência de variáveis ambientais, antropométricas e morfológicas sobre a prestação motora de crianças pré-pubertárias (Marta et al, 2011;Marta, Marinho, Barbosa, Izquierdo, & Marques, 2012). Esta necessidade é especialmente premente no período pré-pubertário em que a frequência de aulas de educação física e de atividades extracurriculares (e.g., clubes desportivos e do desporto escolar e atividades desportivas organizadas) poderá representar um estímulo considerável sobre o desenvolvimento motor da criança (Marta et al, 2012).…”
Section: Introductionunclassified
“…Esta necessidade é especialmente premente no período pré-pubertário em que a frequência de aulas de educação física e de atividades extracurriculares (e.g., clubes desportivos e do desporto escolar e atividades desportivas organizadas) poderá representar um estímulo considerável sobre o desenvolvimento motor da criança (Marta et al, 2012). Face ao atrás exposto, a possibilidade de investigar o efeito de variáveis do domínio biológico e ambiental na prestação motora de rapazes e raparigas pré-púberes poderá enriquecer de forma inequívoca o corpo de conhecimento atual.…”
Section: Introductionunclassified